PAKSAAN EKONOMI DAN PENYALAHGUNAAN KEADAAN SEBAGAI BENTUK CACAT KEHENDAK DALAM PERKEMBANGAN HUKUM KONTRAK - Fani Martiawan Kumara Putra (Universitas Airlangga, 2015)
In fulfillment of a contract, it must be based on good faith and based on the terms of validity of the contract that has been arranged in Burgerlijk Wetboek (BW). One of its requirements is agreed, this agreement apparently has a variety of important aspects, regarding the will. The will is an important part in the validity of a contract, when there is a defect of the will, then the contract would have to see the consequences. Defects of will shall include a compulsion, which lately appeared similar pattern type that called abuse of circumstaces and economic duress. Both of them are not set in BW. This situation is different from compulsion (dwang) in general, yet still have some similarities in their characteristics. Because it is still just a doctrine, then the solution requires prudence and foresight of the judges.